Dingo visitation patterns and behaviour at long-term scent-marking sites suggests a role in mate competition - Brendan F. Alting; Benjamin J. Pitcher; Neil. R. Jordan (Behavioral Ecology and Sociobiology, 2025)
Many carnivores scent mark to communicate with conspecifics, and understanding seasonal and social patterns of scent marking can help to elucidate its function(s). Dingoes are mainland Australia’s apex terrestrial predator, with family groups (‘packs’) defending territories from neighbours and other conspecifics. In contrast to other wild canids such as wolves, coyotes, and African wild dogs, where patterns of scent marking are relatively well studied, little is known about scent marking in wild dingoes. Using camera traps at 10 dingo marking sites within the ranges of multiple dingo packs, we characterised seasonal visitation patterns and detailed scent-marking behaviour. Dingoes visited marking sites more frequently during the annual breeding season (March to May), at which time scent marking rates also increased. When an opposite sex pair visited a marking site together, males scent marked at higher rates than females, and were responsible for most first (60%) and last (73%) scent marks deposited during a visit. Tandem marking – sequential marking by both members of the pair - occurred at 97% of pair visits, and males were significantly more likely to overmark female scent marks than females were to overmark males. Taken together, these results suggest that scent marking plays a role beyond territorial advertisement in dingoes, and supports the hypothesis that male dingoes employ scent marking to mate guard females by advertising their presence/residence to other males, particularly during the annual breeding season. This adds a further example to the literature body on the importance of scent marking in mammalian communication.

Persistent organic pollutants and trace elements detected in New Zealand fur seals (long-nosed fur seal; Arctocephalus forsteri) from New South Wales, Australia, between 1998 and 2019 - Jane Hall; Susan Bengtson Nash; Anil Gautam; Hannah Bender; Benjamin J. Pitcher; Hamish McCallum; Christopher Doyle (Science of The Total Environment, 2023)

The ethics of intervening in animal behaviour for conservation - Thom van Dooren; Catherine J. Price; Peter B. Banks; Oded Berger-Tal; Matthew Chrulew; Jane Johnson; Gabrielle Lajeunesse; Kate E. Lynch; Clare McArthur; Finn C.G. Parker; Myles Oakey; Benjamin J. Pitcher; et al. (Trends in Ecology & Evolution, 2023)

Zoo-bred female birds prefer songs of zoo-bred males: Implications for adaptive management of reintroduction programs - Daniel L. Appleby; Joy S. Tripovich; Naomi E. Langmore; Robert Heinsohn; Benjamin J. Pitcher; Ross Crates (Biological Conservation, 2023)

Allosuckling behavior in the Australian sea lion ( Neophoca cinerea ): An updated understanding - Benjamin J. Pitcher; Heidi Ahonen; Isabelle Charrier; Robert G. Harcourt (Marine Mammal Science, 2011)

Delayed onset of vocal recognition in Australian sea lion pups (Neophoca cinerea) - Benjamin J. Pitcher; Heidi Ahonen; Robert G. Harcourt; Isabelle Charrier (The Science of Nature, 2009)